2014
DOI: 10.1016/j.cyto.2014.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric C-reactive protein and Notch-3 co-operatively increase angiogenesis through PI3K signalling pathway

Abstract: C-reactive protein (CRP) is the most acute-phase reactant serum protein of inflammation and a strong predictor of cardiovascular disease. Its expression is associated with atherosclerotic plaque instability and the formation of immature micro-vessels. We have previously shown that CRP upregulates endothelial-derived Notch-3, a key receptor involved in vascular development, remodelling and maturation. In this study, we investigated the links between the bioactive monomeric CRP (mCRP) and Notch-3 signalling in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 55 publications
3
41
0
2
Order By: Relevance
“…1D ) indicating a potential mechanism for amyloid cleavage. mCRP also phosphorylated ERK and AKT as shown previously (data not included; 13 ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1D ) indicating a potential mechanism for amyloid cleavage. mCRP also phosphorylated ERK and AKT as shown previously (data not included; 13 ).…”
Section: Resultssupporting
confidence: 86%
“…Recombinant forms of both mCRP and nCRP (0.5 mg/mL in 25 mM NaPBS, pH 7.4) was produced in the laboratory of Dr. L.A. Potempa as previously described 8 9 10 13 . The mCRP solution contained an endotoxin concentration lower than 0.125 EU/mL and all cell culture medium was endotoxin-free.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated mCRP ability to promote angiogenesis either in vitro (endothelial cell migration, proliferation and tubulogenesis) or in vivo (chorioallantoic membrane assay) and have determined the main CRP-induced pro-angiogenic genes [34]. In addition, a recent study has demonstrated the ability of CRP to promote angiogenesis via activation of the PI3K/Akt survival pathway [60].…”
Section: Pentraxins In Angiogenesis and Restenosismentioning
confidence: 97%
“…Final concentration of 0.5 mg/mL MTT solution (Sigma Aldrich, St. Louis, MO) was added to each well and incubated for 4 h. After the incubation, formazan crystals were dissolved by addition of 150 μl dimethyl sulfoxide per well. The absorbance was measured at 570 nm using an automated ELISA plate reader (Thermo Scientific ® , Rockford, IL) [16]. …”
Section: Methodsmentioning
confidence: 99%